2004
DOI: 10.1038/sj.bjc.6602233
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 expression and patients survival in lung cancer: systematic review of the literature with meta-analysis

Abstract: Among new biological markers that could become useful prognostic factors for lung carcinoma, Ki-67 is a nuclear protein involved in cell proliferation regulation. Some studies have suggested an association between Ki-67 and poor survival in lung cancer patients. In order to clarify this point, we have performed a systematic review of the literature, using the methodology already described by our Group, the European Lung Cancer Working Party. In total, 37 studies, including 3983 patients, were found to be eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
174
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(199 citation statements)
references
References 72 publications
15
174
2
3
Order By: Relevance
“…[13][14][15][16] Ki-67 is present in all active phases of the cell cycle. We found that Ki-67 was complementary to p53 in identifying patients at risk for early post-transplant hepatocellular carcinoma recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Ki-67 is present in all active phases of the cell cycle. We found that Ki-67 was complementary to p53 in identifying patients at risk for early post-transplant hepatocellular carcinoma recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 expression was associated with prognosis in prostate, breast and lung cancer. [13][14][15][16] In contrast, an inverse association was observed with cervical cancer prognosis 17 and no association was found with prognosis in patients with colon and pancreatic cancer. 18,19 In a study of patients undergoing surgical resection for hepatocellular carcinoma, higher levels of expression of Ki-67 in tumor tissue were associated with higher tumor grade 20 and early disease recurrence.…”
mentioning
confidence: 87%
“…Tumor proliferative activity, in general evaluated by Ki-67 expression, is a prognostic marker in different type of tumours included NSCLC and it is considered of potential interest in defining populations at high or low risk of recurrence [49]. No data are available about the possible correlation between high tumor proliferation and response to EGFR inhibitors.…”
mentioning
confidence: 99%
“…The participation of many readers was a guarantee for the correct interpretation of the articles. The methodological evaluation was scored according to the European Lung Cancer Working Party (ELCWP) scale previously published (Steels et al, 2001) and applied in other meta-analyses (Delmotte et al, 2002;Meert et al, 2002aMeert et al, , b, 2003Martin et al, 2003Martin et al, , 2004Mascaux et al, 2005a). Each item was assessed using an ordinal scale (possible values: 2, 1, 0).…”
Section: Methodological Assessmentmentioning
confidence: 99%
“…In order to clarify the prognostic impact of other biological factors in lung cancer, our group has performed systematic reviews of the literature with meta-analyses. It allowed us to show that VEGF (Delmotte et al, 2002), microvessel density (Meert et al, 2002b), EGFR (Meert et al, 2002a), HER-2/Neu , Ki-67 (Martin et al, 2004), K-Ras (Mascaux et al, 2005a) and p53 (Steels et al, 2001) have a negative impact on survival, whereas Bcl-2 is associated with a favourable survival effect, at least when studying their impact in univariate analysis.…”
mentioning
confidence: 99%